Does body surface area of children affect the oral health? - Raya Rashid Aldafaai; Zainab Juma Jafar; Rasha Khalaf Zighair (Journal of the Pakistan Medical Association, 2024)
Objectives: To evaluate relationship between oral health and body surface area among children. Method: The observational, cross-sectional study was conducted from January to February /2022 after approval from the ethics review committee of the College of Dentistry, University of Baghdad, Baghdad, Iraq, and comprised children of either gender aged 6-8 years who were randomly selected from primary schools in the city. Body surface area was calculated geometrically using different formulas, and the DuBois formula was used to make the intervals. The estimated body surface area values were broadly divided into four intervals: 0.8-0.9, >0.9-1.0, >1.0-1.1, >1.1. Dental caries was examined using the World Health Organisation criteria related to decayed, missed and filled teeth and surfaces for primary and permanent teeth. Dental plaque and gingival health status were measured using plaque and gingival indices. Data was analysed using SPSS 22. Results: There were 240 subjects. There was no significant difference in terms of mean body surface area intervals of decayed, missed and filled teeth and surfaces for primary and permanent teeth (p>0.05). The mean values of gingival index showed significant differences across body surface area intervals (p<0.05). Mean plaque index values showed no significant differences (p>0.05). Conclusion: No relationship between body surface area and caries experience of primary and permanent teeth was found. However, increasing the body surface area increased gingival inflammation. Key Words: Periodontal Index, Oral Health, Dental Plaque, Health Status, World Health Organization, Inflammation